2.Synthesis, crystal structure and magnetic properties of the mixed-ligand complex [Gd(F3CCO2)3(phen)2(H2O)] - Rizzi, Alberto Claudio (2001)
The mononuclear gadolinium mixed-ligand complex [Gd(CF3CO2)3(phen)2(H2O)] has been prepared and structurally characterized by X-ray crystallography. Two complex molecules are doubly bridged by H bonds between carboxylate and aqua ligands with a Gd−Gd separation of 7.16(1) Å. Magnetic susceptibility and EPR measurements showed weak magnetic exchange coupling of the 3D type.